TINGKAT PENGUNGKAPAN WAJIB PERBANKAN SYARIAH DI INDONESIA - Cut Eka Wahyuni; Yossi Diantimala (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2016)
This study aimed to test the level of mandatory disclosure of Islamic banking in SFAS 105 about mudharaba and SFAS 106 about musyarakah. This variable was measured by exposure of Islamic banking to disclose the items contained in SFAS 105 and SFAS 106. Disclosure was measured by the level of adherence to the items of disclosure (mandatory disclosure items) which are arranged in SFAS 105 and SFAS 106. In this research,samplingwas conductedbyusing purposive samplingto obtain a sample according to the criteria. The type of data in this research is secondary data, which is refers to information gathered from existing resources. Collecting data by using documentation technique is the method of data collection which is done by collecting the entire secondary data and all the information that is used to resolve the problems that exist in the document. The results showed that the index of disclosure in SFAS 105 about Mudharabah and disclosure index in SFAS 106 about Musharaka showed that compliance level of index is higher, so the level of disclosure if the required on Islamic banking is higher to as compliance lever.Keywords: Disclosure Index, SFAS 105 About Musharaka, SFAS 106 About Musharaka